2003
DOI: 10.1037/0022-006x.71.3.482
|View full text |Cite
|
Sign up to set email alerts
|

Family-focused treatment versus individual treatment for bipolar disorder: Results of a randomized clinical trial.

Abstract: Recently hospitalized bipolar, manic patients (N = 53) were randomly assigned to a 9-month, manual-based, family-focused psychoeducational therapy (n = 28) or to an individually focused patient treatment (n = 25). All patients received concurrent treatment with mood-stabilizing medications. Structured follow-up assessments were conducted at 3-month intervals for a 1-year period ofactive treatment and a 1-year period of posttreatment follow-up. Compared with patients in individual therapy, those in family-focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
223
1
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 326 publications
(246 citation statements)
references
References 44 publications
10
223
1
12
Order By: Relevance
“…89 Two randomised controlled trials including symptomatic patients with bipolar I and II found that, in the 1-2 years after a manic, mixed, or depressive episode, patients with bipolar disorder who received familyfocused therapy and pharma cotherapy had 30-35% lower rates of relapse and rehospitalisation and less severe symptoms than did patients in case manage ment 28 or equally intensive individual treatment. 63 Two randomised controlled trials in paediatric populations-one in adolescents (aged 12-18 years) with bipolar disorder 64 and one in children and adolescents (aged 9-17 years) with depression or hypomania with a first degree relative with bipolar disorder 65 -found that children and adolescents who received familyfocused therapy and pharmacotherapy recovered more rapidly from depressive episodes (HR 0·37-0·54) than did children and adolescents in brief psychoeducation and pharmacotherapy.…”
Section: Family-focused Therapymentioning
confidence: 99%
“…89 Two randomised controlled trials including symptomatic patients with bipolar I and II found that, in the 1-2 years after a manic, mixed, or depressive episode, patients with bipolar disorder who received familyfocused therapy and pharma cotherapy had 30-35% lower rates of relapse and rehospitalisation and less severe symptoms than did patients in case manage ment 28 or equally intensive individual treatment. 63 Two randomised controlled trials in paediatric populations-one in adolescents (aged 12-18 years) with bipolar disorder 64 and one in children and adolescents (aged 9-17 years) with depression or hypomania with a first degree relative with bipolar disorder 65 -found that children and adolescents who received familyfocused therapy and pharmacotherapy recovered more rapidly from depressive episodes (HR 0·37-0·54) than did children and adolescents in brief psychoeducation and pharmacotherapy.…”
Section: Family-focused Therapymentioning
confidence: 99%
“…Rea ve arkadaşları, Bipolar I tanısı almış 53 yatan hastanın 28 tanesine aileleriyle birlikte psikoeğitim vermiş, 25 kişilik kontrol grubuna ise sadece bireysel psikoeğitim vermişlerdir. [58] Yirmi bir oturumluk Psikiyatride Güncel Yaklaşımlar -Current Approaches in Psychiatry çalışma yaklaşık 9 ay devam etmiş, sonrasında 2 yıllık bir takip çalışması yapılmıştır. Sonuçta aileleri psikoeğitim almış gruptaki hastalarda yineleme sayısı ve hastaneye yatış sayısında anlamlı düzeyde azalma olduğu bulunmuş-tur.…”
Section: Bilişsel Davranışçı Psikoeğitimunclassified
“…92 Over the first year of followup, FFT demonstrated some weakly greater treatment efficacy compared to individual therapy. Over the 2-year study period (including 1 year of treatment and another year of followup) however, FFT was associated with significantly fewer total relapses and fewer hospitalizations.…”
Section: Family-focused Treatmentmentioning
confidence: 99%